2003
DOI: 10.1152/jn.00713.2002
|View full text |Cite
|
Sign up to set email alerts
|

Fast Ca2+-Induced Potentiation of Heat-Activated Ionic Currents Requires cAMP/PKA Signaling and Functional AKAP Anchoring

Abstract: Calcium influx and the resulting increase in intracellular calcium concentration ([Ca(2+)](i)) can induce enhanced sensitivity to temperature increases in nociceptive neurons. This sensitization accounts for heat hyperalgesia that is regularly observed following the activation of excitatory inward currents by pain-producing mediators. Here we show that rat sensory neurons express calcium-dependent adenylyl cyclases (AC) using RT-PCR and nonradioactive in situ hybridization. Ionomycin-induced rises in [Ca(2+)](… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 51 publications
(36 reference statements)
1
24
0
Order By: Relevance
“…The deficiency of IKK␤ in sensory neurons of SNS-IKK␤ Ϫ/Ϫ mice may disturb the balance of these membrane events and explain the observed lower activation threshold of A␦-and C-fibers and the faster response toward mechanical and heat stimulation and enhanced nociceptive responses after capsaicin or Formalin injection. Various kinases, including protein kinase C and A, p38 mitogen-activated protein kinase, and cyclin-dependent kinase Cdk5, were reported to increase TRPV1 channel activity by phosphorylation of individual serine or threonine residues (Ji et al, 2002;Bhave et al, 2003;Distler et al, 2003;Carlton et al, 2004;Zhang et al, 2005;Siemens et al, 2006;Salazar et al, 2008), i.e., exerting opposite effects on the channel than the IKK␤-mediated negative control observed here, suggesting that IKK␤ either affects residues other than those known to increase TRPV1 activity or a mechanism not exerted by direct TRPV1 phosphorylation. The moderate increase of TRPV1 protein in IKK␤-deficient neurons, particularly at their peripheral and central terminals, suggests that IKK may also regulate the expression of TRPV1.…”
Section: Discussionmentioning
confidence: 67%
“…The deficiency of IKK␤ in sensory neurons of SNS-IKK␤ Ϫ/Ϫ mice may disturb the balance of these membrane events and explain the observed lower activation threshold of A␦-and C-fibers and the faster response toward mechanical and heat stimulation and enhanced nociceptive responses after capsaicin or Formalin injection. Various kinases, including protein kinase C and A, p38 mitogen-activated protein kinase, and cyclin-dependent kinase Cdk5, were reported to increase TRPV1 channel activity by phosphorylation of individual serine or threonine residues (Ji et al, 2002;Bhave et al, 2003;Distler et al, 2003;Carlton et al, 2004;Zhang et al, 2005;Siemens et al, 2006;Salazar et al, 2008), i.e., exerting opposite effects on the channel than the IKK␤-mediated negative control observed here, suggesting that IKK␤ either affects residues other than those known to increase TRPV1 activity or a mechanism not exerted by direct TRPV1 phosphorylation. The moderate increase of TRPV1 protein in IKK␤-deficient neurons, particularly at their peripheral and central terminals, suggests that IKK may also regulate the expression of TRPV1.…”
Section: Discussionmentioning
confidence: 67%
“…Unlike the case with rodents, the Bz-sensitive salt taste receptor (presumably ENaC) plays a minor role in human salt taste perception. The predominant component of human salt taste is amiloride-and Bz-insensitive (Feldman et al 2003;Ossebaard and Smith 1995). Thus the identification of the amiloride-and Bz-insensitive salt taste receptor(s), their natural and synthetic agonists, and the physiological mechanisms that regulate salt taste transduction are necessary steps in the discovery of safe and effective salt taste enhancers.…”
Section: Discussionmentioning
confidence: 99%
“…S3C), which is consistent with the observations that cAMP enhances NaCl responses by activating ENaC . Although in some studies PKA simulation has been shown to sensitize TRPV1 (Bhave et al 2002;Distler et al 2003;Mohapatra and Nau 2003;Rathee et al 2002), in other studies PKA activation did not result in an increase in TRPV1 currents (Lee et al 2000;Plant et al 2007). Our studies suggest that in TRCs TRPV1t is constitutively active and phosphorylation of the channel by PKA does not further modulate the channel activity.…”
Section: Modulation Of Trpv1t Activity By Pkcmentioning
confidence: 98%
See 1 more Smart Citation
“…13 and 14). AKAP anchored PKA is required in this process as the Ht31 peptide (a competitor of PKA-AKAP association) blocks forskolin-and PGE 2 -induced TRPV1 sensitization in sensory neurons (15,16). AKAP79/150 is expressed in ϳ80% of TRPV1 positive DRG neurons and directly binds to TRPV1 (17)(18)(19).…”
mentioning
confidence: 99%